Mechanism of HCV's resistance to IFN-α in cell culture involves expression of functional IFN-α receptor 1 - Lamaze Christophe; Koster Mario; Hauser Hansjorg; Wimley William C; Gunduz Feyza; Poat Bret; Samara¹ Maria; Chandra Partha K; Hazari Sidhartha; Datta Sibnarayan; Balart Luis A; Garry Robert F; et al. (Virology Journal, 2011)
Abstract The mechanisms underlying the Hepatitis C virus (HCV) resistance to interferon alpha (IFN-α) are not fully understood. We used IFN-α resistant HCV replicon cell lines and an infectious HCV cell culture system to elucidate the mechanisms of IFN-α resistance in cell culture. The IFN-α resistance mechanism of the replicon cells were addressed by a complementation study that utilized the full-length plasmid clones of IFN-α receptor 1 (IFNAR1), IFN-α receptor 2 (IFNAR2), Jak1, Tyk2, Stat1, Stat2 and the ISRE- luciferase reporter plasmid. We demonstrated that the expression of the full-length IFNAR1 clone alone restored the defective Jak-Stat signaling as well as Stat1, Stat2 and Stat3 phosphorylation, nuclear translocation and antiviral response against HCV in all IFN-α resistant cell lines (R-15, R-17 and R-24) used in this study. Moreover RT-PCR, Southern blotting and DNA sequence analysis revealed that the cells from both R-15 and R-24 series of IFN-α resistant cells have 58 amino acid deletions in the extracellular sub domain 1 (SD1) of IFNAR1. In addition, cells from the R-17 series have 50 amino acids deletion in the sub domain 4 (SD4) of IFNAR1 protein leading to impaired activation of Tyk2 kinase. Using an infectious HCV cell culture model we show here that viral replication in the infected Huh-7 cells is relatively resistant to exogenous IFN-α. HCV infection itself induces defective Jak-Stat signaling and impairs Stat1 and Stat2 phosphorylation by down regulation of the cell surface expression of IFNAR1 through the endoplasmic reticulum (ER) stress mechanisms. The results of this study suggest that expression of cell surface IFNAR1 is critical for the response of HCV to exogenous IFN-α.